2021
DOI: 10.1021/acs.langmuir.0c03056
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Battery to High Performance Pseudocapacitor by the Hybridization of W18O49 with RuO2 Nanostructures

Abstract: Defects such as oxygen vacancy in the nanostructures have paramount importance in tuning the optical and electronic properties of a metal oxide. Here we report the growth of oxygen deficit tungsten oxide (W18O49) nanorods modified with ruthenium oxide (RuO2) using a simple and economical hydrothermal approach for energy storage application. In this work, a novel approach of hybridizing the W18O49 nanostructure with RuO2 to control the electrochemical performance for energy storage applications has been propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Still, it is difficult to stabilize the structure and enhance the electrochemical performance of the cathode material to satisfy the requirements of the practical application. 24,25 Based on the chemical replacement of the prototypical cathode, LiCoO 2 the structure of cathode materials in most of the best performing lithium-ion batteries is layered two-dimensional crystallographic. 26 Fig.…”
Section: Mrmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, it is difficult to stabilize the structure and enhance the electrochemical performance of the cathode material to satisfy the requirements of the practical application. 24,25 Based on the chemical replacement of the prototypical cathode, LiCoO 2 the structure of cathode materials in most of the best performing lithium-ion batteries is layered two-dimensional crystallographic. 26 Fig.…”
Section: Mrmentioning
confidence: 99%
“…Their portability (for smaller sizes) and the capacity to immediately provide electrical power is the most convenient property. 8–10 A single cell of the battery is composed of an electrolyte, a separator, a negative electrode, and a positive electrode as presented in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…However, to meet the greater necessities of upcoming systems, Researchers need to expand their performance by designing novel materials with high energy and power density concurrently. In the past few years, widespread activities have been defined to emphasize for the capable and simplistic progressions to fabricate thin, stretchable, and signifigant solid-state flexible batteries and supercapacitors, which are well thought-out as one of the opted candidates for most promising power sources in many of the portable and microelectronic applications [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…[ 36–38 ] It has also been reported that producing RuO 2 ‐based MMOs might also contribute to the overall stability of the electrode materials. [ 39,40 ]…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38] It has also been reported that producing RuO 2 -based MMOs might also contribute to the overall stability of the electrode materials. [39,40] In this work, Ru-based MMO electrodes containing different ratios of Bi-and Ru-oxide have been produced by thermal decomposition, and the effect of the Ru/Bi ratio on their charge storage/delivery performance is presented. Ru was chosen due to its superior charge storage/delivery capabilities, while Bi-oxide was chosen because of its excellent electrochemical properties, low-cost, and non-toxic nature.…”
Section: Introductionmentioning
confidence: 99%